Analysis of Climate Change Trend in the Lower Kaski District of Nepal - Basnet, Keshav; Shrestha, Anup; Joshi, Prajash Chandra; Pokharel, Nisha (Himalayan Journal of Applied Science and Engineering, 2020)
Climate change is considered as the most critical global challenge of the century. Unusual precipitation pattern and outflanking of hydraulic structures frequently reported these days in the Kaski district of Nepal. This research aimed to analyze the trend of climate change in the lower Kaski using annual and seasonal weather data (2001-2017) of five meteorological stations out of which three on the upper tropical region, one on the sub-tropical region and the other one on the temperate region. Individual trend analysis was performed for rainfall and temperature patterns using Mann-Kendell test. Trend analysis for seasonal average precipitation shows an increasing trend for winter and pre-monsoon seasons and a decreasing trend for monsoon and post-monsoon seasons. In contrast, overall annual precipitation shows a decreasing trend. An increasing trend was found for maximum seasonal temperature for all seasons except pre-monsoon season. The seasonal minimum temperature shows a growing trend and overall annual trends for both the maximum and minimum temperatures were also increasing. All of these trends are the evidence of climatic changes that are happening over time. Additionally, a comparative study was conducted between a meteorological station and a locally established manual station. The differences in the numeric values of cumulative rainfall with comparable precipitation readings suggest the need to take into account local station data for design, construction, and planning of hydraulic structures.